2012
DOI: 10.1161/circulationaha.112.092494
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm Versus Rate Control Therapy and Subsequent Stroke or Transient Ischemic Attack in Patients With Atrial Fibrillation

Abstract: Background-Stroke is a debilitating condition with an increased risk in patients with atrial fibrillation. Although data from clinical trials suggest that both rate and rhythm control are acceptable approaches with comparable rates of mortality in the short term, it is unclear whether stroke rates differ between patients who filled prescriptions for rhythm or rate control therapy. Methods and Results-We conducted a population-based observational study of Quebec patients Ն65 years with a diagnosis of atrial fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 38 publications
0
66
1
2
Order By: Relevance
“…9 The prevalence of stroke risk factors in the study population was similar to that reported in the RE-LY 4 and PROTECT AF 7 studies, as well as the general Canadian population. 10 The prevalence and incidence of patient comorbidities in the study population, including diabetes mellitus, hypertension, coronary artery and cerebrovascular disease, heart failure, liver disease, renal disease, alcohol consumption, and prior bleeding, were incorporated into the model given their impact on current and subsequent stroke and bleed risk (Table 1). 1,9,[11][12][13] …”
Section: Base Casementioning
confidence: 99%
“…9 The prevalence of stroke risk factors in the study population was similar to that reported in the RE-LY 4 and PROTECT AF 7 studies, as well as the general Canadian population. 10 The prevalence and incidence of patient comorbidities in the study population, including diabetes mellitus, hypertension, coronary artery and cerebrovascular disease, heart failure, liver disease, renal disease, alcohol consumption, and prior bleeding, were incorporated into the model given their impact on current and subsequent stroke and bleed risk (Table 1). 1,9,[11][12][13] …”
Section: Base Casementioning
confidence: 99%
“…Restoration of a sinus rhythm is considered to improve the long-term survival rates and reduce the incidence of stroke/TIA in general AF patients (22,23). In addition, a previous observational study indicated that catheter ablation is superior to AADs in reducing the all-cause mortality rate (24).…”
Section: Discussionmentioning
confidence: 99%
“…23 They found that the stroke risk was significantly lower in the rhythm control group than in the rate control group, and such a tendency was more prominent in patients with CHADS2 (congestive heart failure, hypertension, age ≥75 years, diabetes mellitus, and previous stroke) >1. With regard to stroke risk, distinction of AF patients in whom rhythm control is more effective, is an important issue.…”
Section: Paf Scorementioning
confidence: 97%